Reply to second comments on "Radiation from fast and slow traveling waves" - Sutinjo, Adrian; Okoniewski, M.; Johnson, R. (2009)
We thank Dr. Tomiyasu for his continued interest and questions. To facilitate our response, we have introduced the following groups based on the comments above: A. Questions and comments directly related to the content of our reply to comment [1]. B. The mode(s) that is/are supported in a slit waveguide, i.e., TE1,0 or TE0.5,0? C. Experimental validations. © 2009 IEEE.